Niche evolution and phylogenetic community paleoecology of late Ordovician crinoids - Cole, Selina R. (Cambridge University Press, 2022)
Fossil crinoids are exceptionally suited to deep-time studies of community paleoecology and niche partitioning. By merging ecomorphological trait and phylogenetic data, this Element summarizes niche occupation and community paleoecology of crinoids from the Bromide fauna of Oklahoma (Sandbian, Upper Ordovician). Patterns of community structure and niche evolution are evaluated over a ~5 million-year period through comparison with the Brechin Lagerstätte (Katian, Upper Ordovician). The authors establish filtration fan density, food size selectivity, and body size as major axes defining niche differentiation, and niche occupation is strongly controlled by phylogeny. Ecological strategies were relatively static over the study interval at high taxonomic scales, but niche differentiation and specialization increased in most subclades. Changes in disparity and species richness indicate the transition between the early-middle Paleozoic Crinoid Evolutionary Faunas was already underway by the Katian due to ecological drivers and was not triggered by the Late Ordovician mass extinction.